Individual short‐acting opioids and the risk of opioid‐related adverse events in adolescents. Issue 11 (16th August 2019) - Chung, Cecilia P.; Callahan, Stephen Todd; Cooper, William O.; Dupont, William D.; Murray, Katherine T.; Franklin, Andrew D.; Hall, Kathi; Dudley, Judith A.; Stein, Charles Michael; Ray, Wayne A.
Abstract: Purpose: Hydrocodone, codeine, oxycodone, and tramadol are frequently prescribed to adolescents for moderate pain related to minor trauma or dental, surgical, or medical procedures. Pharmacokinetic and pharmacodynamic differences between these opioids could affect their relative safety. We aimed to compare occurrence of opioid‐related adverse events in adolescents without cancer or other severe conditions taking hydrocodone, codeine, oxycodone, and tramadol. Methods: Retrospective cohort study of 201 940 Tennessee Medicaid enrollees 12 to 17 years of age without cancer, other severe conditions, or evidence of substance abuse with 529 731 filled prescriptions for study opioids. Adverse events were defined as an emergency department visit, hospital admission, or death related to opioid use, confirmed by medical record review. Serious events had opioid‐related escalation of care, hospitalization, or death. Propensity‐score adjusted hazard ratios (HRs) were calculated with hydrocodone as the reference category. Results: The incidence of opioid‐related adverse events per 10 000 person‐years of opioid exposure was 97.5 for hydrocodone (127 events/13 026 person‐years), 91.2 for codeine (58/6, 359), 229.7 for oxycodone (43/1, 872), and 317.7 for tramadol (47/1479). The HRs for tramadol in comparison with hydrocodone for all and serious events were 2.98 (2.03‐4.39) and 2.94 (1.81‐4.75), respectively. Increased risk for tramadol was consistently present when the adverse events were restricted to those with neurologic‐respiratory depression/other symptoms of possible overdose. Conclusion: In adolescents without cancer or other severe conditions prescribed short‐acting opioids, the incidence of both all opioid‐related adverse events and more serious events with opioid‐related escalation of care, hospitalization, or death was consistently greater for tramadol than for hydrocodone.